The role of achievement goals and identity in academic performance and misconduct of college athletes: Considering sport-to-school spillover - Mariya A. Yukhymenko-Lescroart (Heliyon, 2023)
This study examined the role of achievement goal orientations (academic mastery and performance, athletic task and ego) and identity (academic and athletic) in the academic performance and misconduct of Division I student-athletes (N = 1151). Results of the structural equation modeling showed that academic performance was predicted positively by academic performance goal and academic identity (both directly and indirectly through performance goal) and negatively by athletic identity. Academic misconduct was predicted negatively by both self-referenced goals (academic mastery and athletic task), but positively by athletic ego goal. A positive indirect relationship was found between academic identity and academic misconduct through academic mastery goal. Opposing indirect relationships were found between athletic identity and academic misconduct through task and ego goals, which canceled each other out. Taken together, findings highlight the importance of fostering strong academic identities and setting self-referenced goals in school and sport for the academic success of Division I student-athletes.